1995
DOI: 10.1002/j.1551-8833.1995.tb06347.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic removal by coagulation

Abstract: This utility's goal of 90 percent arsenic removal was attained through treatment with 6.5 mg/L ferric chloride. This study evaluated the removal of naturally occurring arsenic in a full‐scale (106‐mgd) conventional treatment plant. When the source water was treated with 3–10 mg/L of ferric chloride or 6, 10, or 20 mg/L of alum, arsenic removal was 81–96 percent (ferric chloride) and 23–71 percent (alum). Metal concentrations in the sludge produced during this study were below the state's current hazardous wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(49 citation statements)
references
References 13 publications
1
48
0
Order By: Relevance
“…For As(V), the increase in ionic strength from 0.001 to 0.1 M leads to a shift in the position of the pH edge toward the alkaline region (Fig. 4a), and slightly enhances adsorption in this range (7)(8)(9)(10). These behaviors are indicative of an inner-sphere adsorption mechanism for As(V) on the Fe-Zr binary oxide.…”
Section: Effect Of Ph and Ionic Strengthmentioning
confidence: 91%
See 1 more Smart Citation
“…For As(V), the increase in ionic strength from 0.001 to 0.1 M leads to a shift in the position of the pH edge toward the alkaline region (Fig. 4a), and slightly enhances adsorption in this range (7)(8)(9)(10). These behaviors are indicative of an inner-sphere adsorption mechanism for As(V) on the Fe-Zr binary oxide.…”
Section: Effect Of Ph and Ionic Strengthmentioning
confidence: 91%
“…As(III) is much more toxic [5], soluble, and mobile than As(V). A variety of treatment processes such as coagulation/precipitation [6,7], ion-exchange [8], adsorption [4,9,10], and membrane processes [8,11] have been employed to remove arsenic. Adsorption methods are considered to be the most promising technologies because the system can be simple to operate and cost-effective [10].…”
Section: Introductionmentioning
confidence: 99%
“…For arsenite, the uncharged H 3 AsO 3 dominates at pH lower than 9.0 under reducing conditions (Yan et al, 2000;Smedley and Kinniburgh, 2002). Various treatment techniques such as coagulation/precipitation (Scott et al, 1995), ion-exchange (Kartinen and Martin, 1995), sorption (Jang et al, 2006;Zhang et al, 2007a) and membrane processes (Kartinen and Martin, 1995;Waypa et al, 1997) have been developed and employed for arsenic removal. Due to its simplicity, high efficiency and cost-effectiveness, sorption processes are regarded as the most promising methods and largely used for arsenic removal from water and wastewater (Jang et al, 2006;.Sharma and Sohn, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows the effect of the dosage of ferric chloride on arsenic removal, with an initial arsenic concentration of 0.11-0.120 mg·L Previous studies have shown that the percentage of arsenic removed using alum and ferric chloride coagulation is independent of initial arsenic (V) concentration for a wide range of conditions. Scott [25] showed nearly constant arsenic removal percentages, 82%-96%, when using 3-10 mg·L …”
Section: Optimum Dosementioning
confidence: 95%